Cup-marked Stones in Strathtay, Perthshire - Dixon, John H (Proceedings of the Society of Antiquaries of Scotland, 1922)
Cup-marked stones at a variety of sites are described. The stone at Bailandun is partly embedded in a burial mound. At Balnabeggan the stone has 59 cups, some of which are connected by grooves. Stones from Glen Brerachan and Balvaran which were previously reported are illustrated here. A stone known as the Priest's Basin has a 'cup' measuring 2 feet in width and is thought to have an Early Christian origin.